Development and Initial Validation of a Spiritual Support Subscale for the MOS Social Support Survey - Levine, Ellen G. (Journal of religion and health, 2015)
While spirituality and religious practices are important in coping with illness or other crises, there are few ways of assessing support that people receive from members of their spiritual communities. The goal of this study was to validate a new spiritual support subscale for the Medical Outcomes Study Social Support Scale (MOS-SSS). Questions for the subscale were formed based on responses of 135 breast cancer survivors who were interviewed about their cancer experience. Exploratory factor analysis resulted in four specific factors for the MOS-SSS: emotional/informational, tangible, affectionate, and spiritual support. The new spiritual support subscale has adequate reliability and validity and may be useful in assessing an area of support that is not always addressed.